Expressões do conservadorismo moral na atualidade: a culpabilização de famílias beneficiárias do Programa Bolsa Família - Eufrásio, Amanda (2019)
The investigation of the moralization of the social issue from an income transfer program, such as the “Bolsa Família” Program, is the focus of this research. It was based on the assumption that the expansion of the program in the country resulted in daily manifestations, based on moralism, in relation to the most impoverished people, whose objective was to identify and analyze the elements of neo-conservatism that substantiate the opinions of common sense. We come, then, to the moral conservatism present in these contents. For this research, in addition to the bibliographic research carried out on the subject, the qualitative methodology was used to collect data on internet blogs where they are published and available for sharing in digital social networks, opinions about people who are beneficiaries of the “Bolsa Família” Program. The data were selected between the second semester of 2014 and the first semester of 2018, we selected publications with verbal and non-verbal language that refer to beneficiaries of the “Bolsa Família” Program, based on prejudices and neoconservative ideology, using Internet search engines and key words. It is the continuity of a research on neo-conservatism and its expressions in the professional practice of Social Assistants, initiated in the Masters, and that we chose to extend the analysis out of the professional field, without totally dissociating itself from it. From this, we infer the correspondence of the collected material with stereotypes / stigmas that are often attributed to the beneficiary families of the “Bolsa Família” Program. In the first chapter, we deal with the roots of conservative thinking and its main characteristics. In the second chapter, we locate some important historical landmark of the process of development of conservative ideology, in addition to the assumptions of what we are calling neo-conservatism. In the third chapter, we discuss moral conservatism, based on moral meanings, the constitution of prejudices and moralism, as well as moralization as a means of coping with the social question in Brazilian society. In the fourth and last chapter, we present and analyze the data, from which we arrive at values such as meritocracy, hierarchy, traditional family, order, antistatism, individualism, freedom under the neoliberal perspective, among others, that gain relevance in neoconservative thought and appear in the prejudiced opinions about people beneficiaries of the “Bolsa Família” Program. In addition, we find that neo-conservatism and its theorists, representatives and supporters, from their origin, take morality as the foundation of society and the social issue. We also confirm our research hypothesis that a large part of the opinions about beneficiaries of the “Bolsa Família” Program are based on moral conservatism